A review of heavy metals contamination in traditional medicinal products - Helal Uddin, A.B.M.; Khalid, Reem S.; Khan, Umeed Ali; Abbas, Syed Atif (Intellectual Consortium of Drug Discovery & Technology Development Inc., SK Canada, 2013)
Traditional medicine (TM) has been used since ages, during the past few decades there was a notable global increase in TM usage. According to the World Health Organization (WHO) around 70% of world population relies on traditional healing system for their basic health care needs. The broad use of TM has highlighted many issues subjected to the efficacy and safety of such products. Some TM products contain toxic materials such as heavy metals. Exposure to heavy metals such as arsenic (As), cadmium (Cd), lead (Pb), nickel (Ni), zinc (Zn) and iron (Fe) can cause adverse health effects and toxicity. This article explains, several possibilities for the presence of heavy metals in TM, the toxicity of some heavy metals and a number of reported clinical cases regarding to heavy metals toxicity due to the consumption of TM products from different parts of the world.